Association between maternal body mass index and hospital admissions for infection in offspring: longitudinal cohort study - Claire Carson; Maria A Quigley; Victoria Coathup; Gillian Santorelli; Helen Ashdown (BMJ Medicine)
Objective To investigate the relation between maternal body mass index and hospital admissions for infections in their offspring, and to identify potentially modifiable mediators.Design Longitudinal cohort study.Setting Born in Bradford longitudinal, multi-ethnic birth cohort, Bradford, UK. Secondary analysis linked to routine hospital admission data, January 2007 to 3 October 2022.Participants 9540 singleton births between 2007 and 2011, born to 9037 mothers, followed up from birth to about age 15 years.Main outcome measures Total number of hospital admissions related to infections, between birth and age 15 years, in age categories <1 year, 1-4 years, and 5-15 years.Results The main study cohort comprised 9540 children and 9037 mothers. About 56% of mothers were overweight or obese. First trimester maternal body mass index was positively associated with rates of hospital admissions for infection across all ages, but associations were significant (P<0.05) only for children born to women with the highest body mass index (obesity grades 2-3). Compared with women with a healthy body mass index, children born to women with obesity grades 2-3 had an adjusted rate ratio of 1.41 (95% confidence interval 1.13 to 1.77) at <1 year and an adjusted rate ratio of 1.53 (1.19 to 1.98) for hospital admissions for infection by age 5-15 years. Similar trends were seen for respiratory and gastrointestinal infections, and multisystem viral infections. Being born by caesarean section and child obesity at aged 4-5 years accounted for 21% and 26% of the association, respectively.Conclusions In this study, a modest but consistent association between maternal obesity (grades 2-3) and hospital admissions for infection throughout childhood was found. Healthcare professionals and public health campaigns should continue to support mothers to achieve and maintain a healthy body weight before conception and during the postpartum period.